An energy consumption approach in a manufacturing process using design of experiments. Issue 11 (2nd November 2018) - Guerra-Zubiaga, David A.; Mamun, Abdullah Al; Gonzalez-Badillo, Germanico
ABSTRACT: Modern manufacturing facilities are facing several challenges, such as increasing demand of products with higher flexibility created in the shortest time. Manufacturers must also deal with the efficient use of energy, emission reduction and comply with increasing requirements in sustainability, leading to the development of more efficient processes and systems. A novel environmentally benign manufacturing approach is presented, where production processes and systems move towards a reduced carbon footprint impact. At the factory level, especially in machining, nearly 90% of carbon footprints occur due to the electricity demands of machine tools. At the machining stage, electrical demand is associated with machine start-to-stop, and significantly higher amounts of non-cutting energy are consumed compared with the actual material removal energy in end-milling, resulting in a low efficiency process. The purpose of this paper is to explore machining strategies by analysing energy consumption using Design of Experiments at the material removal rate, to compare cutting trajectories according to parameters, such as spindle speed, feed rate, depth of cut per pass and total depth of cut. It is essential to investigate how different geometrical designs and machining parameters can influence energy consumption in milling operations, and seek potential ways to minimize it.